2018
DOI: 10.15562/bdv.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of condyloma acuminata profile in outpatient clinic of dermato-venereology Sanglah General Hospital Denpasar, Bali-Indonesia period 2015-2017

Abstract: Introduction: Condylomata acuminata (CA) is human papillomavirus (HPV) infection, and one of the most common sexually transmitted disease, characterized with papul or papillomatous nodule in genital, perineum and anal, this disease can be asymptomatic as well. Some study proved sexually transmitted infection increases the incidence of Human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS), and vice versa. Management of CA is Trichloroacetic acid (TCA), Tincture Podophyllin, and Electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…In this study the highest incidence of CA was observed in subjects aged 20-29 years old (28.2%). 9 A previous study on CA by de Peder et al found the highest incidence of CA in the heterosexual group (36.7%), while Piketty et al reported its incidence in the homosexual group was 85-93%. 10,11 We also obtained the highest number of CA without HIV in the heterosexual group (37.2%) and in the homosexual group (25.6%) for CA with HIV.…”
Section: Discussionmentioning
confidence: 92%
“…In this study the highest incidence of CA was observed in subjects aged 20-29 years old (28.2%). 9 A previous study on CA by de Peder et al found the highest incidence of CA in the heterosexual group (36.7%), while Piketty et al reported its incidence in the homosexual group was 85-93%. 10,11 We also obtained the highest number of CA without HIV in the heterosexual group (37.2%) and in the homosexual group (25.6%) for CA with HIV.…”
Section: Discussionmentioning
confidence: 92%
“…A study conducted at the Sanglah Hospital in Bali in 2015-2017 reported increased prevalence and a higher prevalence in males than females. 3 The incidence ratio of males and females was 1: 1.4. 1 The peak age of incidence was 24 years in females and 25-29 years in males.…”
Section: Discussionmentioning
confidence: 95%
“…This was supported by a study conducted at the Bali Sanglah Hospital in 2015-2017, and it reported a higher prevalence in males than females. 3 Men who sex with men (MSM) and transgender women have a high risk of being affected by Human Immunodeficiency Virus (HIV) and often accompanied by HPV co-infection in the anal, penis, and oral regions, including infections with high-risk HPV serotypes. 4,5 Risk factors for anal HPV infection include receptive anal intercourse (RAI), smoking, immunosuppression, and numbers of sexual partners and injection drug use.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence recurrent is 110 per 100.000 persons. 4 The incidence new cases of condyloma acuminata in Bali, Indonesia during period 2015-2017 was 260 of 4743 persons (5.47%) 5 and in Surabaya, Indonesia during 2009-2011 was 259 per 2,960 persons (8.7 %) and 2012-2014 was 318 per 3,674 persons (8.7%). 6 Condyloma acuminata are usually found in warm and moist mucosal regions, that is characterized of skin in the region of anal and genital.…”
Section: Introductionmentioning
confidence: 99%